A Reliability Generalization Meta-Analysis of the Antisocial Process Screening Device - Meng-Cheng Wang; Jiaxin Deng; Xintong Zhang; Jinghui Liang; Yiyun Shou (Behavioral Sciences, 2025)
Although the Antisocial Process Screening Device (APSD) is one of the most widely used instruments for assessing psychopathic traits, the reliability estimates of the APSD show great heterogeneity across different studies. This investigation evaluated the reliability of the APSD using a reliability generalization meta-analytic technique across 158 studies (N = 75,749). The APSD demonstrated marginal to acceptable coefficient alphas ranging from 0.62 (for the Callous–Unemotional subscale) to 0.79 (for the total scale). Further moderation analysis revealed that the differences in administration formats significantly explained the variance of coefficient alphas for the APSD total and subscales, and the self-report version of the APSD manifested poorer coefficient alphas than other-report versions. The standard deviation of scale scores also partly accounted for the variance of the coefficient alphas. Overall, the APSD was found to be a reliable, practical measurement of psychopathic traits in youth, which can be widely applied in various study settings. Nevertheless, we recommend that parent- and teacher-report versions of the APSD as the preferred administering format of the measure when used for children and juveniles, while the self-report version of the APSD is recommended with caution when assessing youth psychopathy, unless multiple-assess methods are used.